An Impact of EMIR on EU Financial Markets - Finkelshtein, Ekaterina (2017)
On 4 July 2012, the Regulation on OTC Derivatives, Central Counterparties and Trade Repositories (known as "EMIR") - European Market Infrastructure Regulation) was adopted and entered into force on 16 August 2012. The Regulation requires standard derivative contracts to be cleared through Central Counterparties (CCPs) as well as margins for uncleared trades and establishes stringent organizational, business conduct and prudential requirements for these CCPs. The regulation also ensures that information on all European derivative transactions will be reported to trade repositories and be accessible to supervisory authorities, including the European Securities and Markets Authority (ESMA), to give policy makers and supervisors a clear overview of what is going on in the markets. The aim of this bachelor thesis is to perform a complex analysis of the impact of EMIR. The first part focuses on empirical research of the regulation. In the second part results of a data analysis from both quantitative and qualitative approach are presented.